Overhauling watershed programme: towards reforms - Shah, Mihir (2006)
The report of the Technical Committee on Watershed Programmes (the Parthasarathy Committee) on watershed reforms recommends a reformed and expanded activity which holds the key to livelihood security. it analyses the drawbacks of the current Hariyali guidelines - a panchayat-centered watershed programme-and emphasises the major role of civil society in guiding reforms in the state sector. This article is a synoptic view of the main findings and recommendations of the report. - Reproduced.
Keywords: Watersheds